Combating Money Laundering and the Financing of Terrorism - A Comprehensive Training Guide : Workbook 3a. Regulatory and Institutional Requirements for AML/CFT - World Bank (World Bank, 2012)
"Combating Money Laundering and the Financing of Terrorism: a Comprehensive Training Guide" is one of the products of the capacity enhancement program on Anti-Money Laundering and Combating the Funding of Terrorism (AML/CFT), which has been co-funded by the Governments of Sweden, Japan, Denmark, and Canada. The program offers countries the tools, skills, and knowledge to build and strengthen their institutional, legal, and regulatory frameworks to successfully implement their national action plan on these efforts. This workbook includes seven training course modules: effects on economic development and international standards (module one); legal requirements to meet international standards (module two); regulatory and institutional requirements for AML/CFT (module three a ); compliance requirements for financial institutions (module three b); building an effective financial intelligence unit (module four); domestic (interagency) and international cooperation (module five); combating the financing of terrorism(module six); and investigating money laundering and terrorist financing (module seven).